Impact of Natural Reserves on the Rehabilitation of the Arabian Oryx in the Protected Areas of Mahazat as-Sayd and Uruq Bani Ma’arid, Kingdom of Saudi Arabia from 1980 until 2011 - ALBAQAMI, TARFAH SAYER MAJED (Journal of Humanities & Social Sciences, 2018)
A limited number of studies have been conducted to evaluate the role of natural reserves in the conservation of the Arabian oryx in the KSA. The two reserves that accommodate the oryx in the country – Mahazat as-Sayd and Uruq Bani Ma’arid – have different environmental attributes, and so impact the species differently. To assess these impacts, five key steps were taken: 1) map-generation for the protected areas and of the Arabian oryx populations in GIS format to aid site and management evaluations; 2) a comparison of natality and mortality rates; 3) the identification of reasons behind the population trends in the two protected areas; 4) a brief investigation of the causes of the wild extinction of the oryx in the KSA; and 5) recommendations for future conservation, protection and management of the reserves and the species. It was revealed that natality and mortality rates in the two reserves are not directly comparable, since Mahazat as-Sayd is a fenced area, while Uruq Bani Ma’arid is a free-range region. It was expected that, in Mahazat as-Sayd, population growth would be a struggle, as this was the start-up location for the Arabian oryx rehabilitation project in the KSA. The lessons learned from the Mahazat as-Sayd project were applied to Uruq Bani Ma’arid, and this is one of the reasons why Uruq Bani Ma’arid has had a more stable population growth. At present, the challenge to the managers of the reserves, and the national government of the KSA, is how to manage conservation efforts for the species going forward, given drastic and extreme climate change. Global support in strengthening research innovations through study aids or grants is recommended at the international level, while the incorporation of nature and wildlife conservation into all levels of education curricula is recommended at the national level.